Experimental investigation of current forces on floating cylinder during the sinking process. (15th April 2019) - Yang, Hanbin; Yang, Wanli; Li, Qiao; Kou, Jing
Abstract: The three dimensional flow around a floating cylinder during the sinking process is influenced by the free surface, the free end and the riverbed or seabed, which result in complicated current forces on the floating cylinder. The physical experiments were carried out to investigate the drag forces, transverse forces, vertical forces, and as well as frequencies of the transverse and vertical forces during the sinking process. The aspect ratio ( AR ) of the submerged depth to the diameter of the model cylinder varies from 0.25 to 1.5 and the Reynolds number (Re) ranges from 2 × 10 4 ∼ 1.2 × 10 5 . Results show that drag coefficients, root mean square coefficients of drag and transverse forces generally increase with AR, and increase significantly at the instant when the free end touches the seabed, which should receive extra attention during the sinking process of cylinder. The vertical force ratio decreases with AR. Fluctuation frequency of the transverse force increases with AR but fluctuation frequency of vertical force is basically not affected by AR . Also the pressure distributions on the front, rear and bottom surfaces of the cylinder were measured and further analyzed to provide a better understanding of the variation of current forces with AR and Re. Highlights: C d increases with AR, and increases slightly with Re when 0.25 ≤  AR ≤1, but decreases to a plateau when 1 <  AR ≤1.5. C d r m s ¯ increases with Re, and decreases slightly with AR when 0.25 ≤  AR ≤0.75, but increases with AR when 0.75 ≤  AR ≤1.5. C l r m s ¯ generally increases with AR and decreases with Re. Vertical force decreases with AR and increases with Re. Drag force and transverse force increase sharply when the floating caisson bottom cuts into the riverbed or seabed.